Menstrual cycle stage and oral contraceptive effects on anterior tibial displacement in collegiate female athletes - Hicks-Little, C. A.; Thatcher, J. R.; Hauth, J. M.; Goldfuss, A. J.; Cordova, M. L. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The aim of this study was to establish if differences in anterior tibial displacement exists in collegiate female student-athletes at different stages of the menstrual cycle. Methods: Design and setting: a 2 x 3 factorial design with repeated measures on the second factor guided this study. The first independent variable was group with 2 levels (control and oral contraceptive) and the second independent variable was menstrual cycle phase with 3 levels (follicular, ovulation, luteal). The single dependent variable was anterior tibial displacement. All data were collected in a research laboratory. Subjects: 53 female student athletes (control: n=28; oral contraceptive: n=25) with no previous history of knee injury or anomalies with a normal 28-30 day menstrual cycle participated. Measurements: anterior tibial displacement (mm) measurements were taken on days 1 (follicular phase), 13 (ovulation phase), and 23 (luteal phase) of each subject's menstrual cycle using a KT1000 ™ knee arthrometer. Results: For the entire group, statistically significant increases in anterior tibial laxity were found (F=4.49; df=52.1; P<0.05) between the follicular cycle (0±SD =5.14 mm) and ovulation cycle (0±SD=5.81 mm); and follicular cycle (0±SD=5.14 mm) and luteal cycle (0±SD=5.79 mm). A separate analysis of the non-birth control group revealed no significant difference in anterior tibial laxity throughout the stages of the menstrual cycle. Conclusion: The results of this study suggest that: 1) the menstrual cycle does have an influence on laxity of the anterior displacement of the knee; 2) significant increases in anterior displacement are shown during the ovulation and luteal phases of the menstrual cycle; and 3) birth control subjects tend to have increased laxity when compared to those subjects who are not on hormone therapy.